Rytme og netværk i Homo Metropolis: Serialisering i Nikoline Werdelins tegneseriestribe - Kühn Paulsen, Felix (Passage - Tidsskrift for litteratur og kritik, 2018)
This article investigates serialization in newspaper comic strips (exemplified by Danish Nikoline Werdelin’s strip Homo Metropolis) with a dual focus on publication structure and composition of individual strips. Reading the forms of Rhythm and Network as symptoms of serialization, the analysis seeks to outline the difference between meeting the comic strip in daily newspapers or in collected books. Furthermore, it investigates how the actual punchlines takes form through constant fluctuation between repetition and interruption. In this way, the article reads Homo Metropolis as an example of how serialized storytelling constantly negotiates the tension between the individual story/punchline and larger network of narratives.